PENDEKATAN KONSELING UNTUK LANSIA - Hermi Pasmawati (Institut Agama Islam Negeri Bengkulu, 2017)
Elderly is the last period of the stage of human development, not everyone is able to pass this period. The characteristics of this stage are unique and distinctive, requiring counseling approaches and techniques relevant to their specific circumstances. In the elderly period many changes occur, ranging from changes in physical conditions are decreased, the function of organs that are not as strong as it used to be, as well as reduced or limited energy to perform activities that are favored. This of course raises its own problems in the elderly. In addition, the reduced functioning condition of the sense of hearing and vision must be one of the obstacles in social interaction, which is the main need for the elderly, the diminishing of friends of the same age, the departure of spouses and children who are independent and separate living make the elderly feel lonely. With the complexity of characteristics that occur in the elderly period, the need for services in the form of psychological and counseling, using approaches relevant to the conditions of uniqueness of the elderly, in this case there are three approaches used in conducting counseling process of the elderly, namely; 1) Classical Psychoanalystic Approach, used in exploratory phase of client problem, 2) Reality approach used in coaching stage or client problem solving and 3) Logoteraphy (Religius) Approach used in coaching stage or client problem solving.